Do Genetic Factors Predispose People to COVID-19: A Review Article - Nasrolahi, Ava; Haghani, Karimeh; Gheysarzadeh, Ali; Bakhtiyari, Salar (Current Molecular Medicine, 2021)
The pandemic of coronavirus disease 2019 (COVID-19) has become a threat to human life and society. Scientists and clinicians are struggling with the intrusive SARS-CoV-2 virus to enhance their knowledge about its pathogenesis and find an effective medicine and vaccine to combat its complications. Till now, they have learned that this SARS-CoV-2 has not infected all people exposed to this virus, and also severe respiratory illnesses have not been observed in all infected patients. Patients over 65 or with underlying diseases are more vulnerable to develop severe disease. Based on this premise, a highly challenging question is why some people are more susceptible to this virus and others are not. The present study was aimed to review the current information, which explains the broad spectrum of COVID-19 presentation. Here, we discussed how genetic background, immune system, underlying disease, smoking status, as well as age, race, and gender affect COVID-19 susceptibility.
Keywords: Genetic susceptibility